Host-dependent C-to-U RNA editing in SARS-CoV-2 creates novel viral genes with optimized expressibility - Zhang, Pirun; Zhang, Wenli; Li, Jiahuan; Liu, Huiying; Yu, Yantong (Frontiers in Cellular and Infection Microbiology, 2024)
Rampant C-to-U RNA editing drives the mutation and evolution of SARS-CoV-2. While much attention has been paid to missense mutations, the C-to-U events leading to AUG and thus creating novel ORFs were uninvestigated. By utilizing the public time-course mutation data from the worldwide SARS-CoV-2 population, we systematically identified the “AUG-gain mutations” caused by C-to-U RNA editing. Synonymous mutations were of special focus. A total of 58 synonymous C-to-U sites are able to create out-of-frame AUG in coding sequence (CDS). These 58 synonymous sites showed significantly higher allele frequency (AF) and increasing rate (dAF/dt) than other C-to-U synonymous sites in the SARS-CoV-2 population, suggesting that these 58 AUG-gain events conferred additional benefits to the virus and are subjected to positive selection. The 58 predicted new ORFs created by AUG-gain events showed the following advantages compared to random expectation: they have longer lengths, higher codon adaptation index (CAI), higher Kozak scores, and higher tRNA adaptation index (tAI). The 58 putatively novel ORFs have high expressibility and are very likely to be functional, providing an explanation for the positive selection on the 58 AUG-gain mutations. Our study proposed a possible mechanism of the emergence of de novo genes in SARS-CoV-2. This idea should be helpful in studying the mutation and evolution of SARS-CoV-2.